Aplicativo para dimensionamento de vigas de concreto armado - Silva, Eugênio dos Santos e (2024)
This work presents the development of a web application, named AppCalc, designed for the sizing of reinforced concrete beams, aiming to provide an accessible and accurate tool for engineers and students. Utilizing HTML, JavaScript, and Python, the application enables structural calculations and generates detailed images of the beams, adhering to the guidelines of NBR 6118:2023. The validation of AppCalc was conducted by comparing its results with those obtained manually and with the Eberick software. The results showed high consistency among the methods, confirming the application's reliability. The small variation observed in calculations was attributed to rounding differences, with no significant impact on accuracy. It is concluded that AppCalc is an innovative solution capable of integrating different programming languages and providing results comparable to traditional methods and established market tools. Thus, AppCalc significantly contributes to civil engineering practice by facilitating structural sizing efficiently and safely.